Pengaruh Kepemimpinan, Lingkungan Kerja dan Kompensasi terhadap Motivasi Kerja Pada PT. Mahkota Group Tbk Medan - Sungguh Ponten Pranata (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
This study aims to determine and analyze the influence of leadership and work environment on employee motivation either partially or simultaneously. The population of this study were employees of PT Mahkota Group Tbk - Medan as many as 53 employees. The sample in this study will use saturated sampling, meaning that the research will be conducted on all employees of PT Mahkota Group Tbk - Medan as many as 53 employees where researchers are not included in this number. The data collection technique in this research is a questionnaire. While the data analysis technique used is the classical assumption test, multiple regression, t test, and F test and determinant coefficient. Leadership has a positive and significant effect on employee motivation. Work environment has a positive and significant effect on employee work motivation. Compensation has a positive and significant effect on employee work motivation. Leadership, work environment and compensation have a positive and significant effect on employee motivation at the PT Mahkota Group Tbk - Medan.